EMOTIONAL PERCEPTION OF THE WORLD BY PRESCHOOL CHILDREN IN THE CONTEXT OF KEY CONCEPTS - Demydova, Yulia (Theoretical and Methodical Problems of Children and Youth Education, 2023)
The article examines the emotional perception of the world by preschool children in the context of key concepts. The purpose of the research is to highlight the key concepts of emotional perception of the world by preschool children. In accordance with the goal, the tasks of defining the basic concepts of “emotions”, “emotional reactions”, “emotional states”, “emotional perception of the world by preschool children”, “world”, typification and characterization of emotions were solved. In order to solve the research tasks, the methods of analysis of scientific sources, comparison, and study of experience, generalization and systematization of materials on the research problem were used Based on the analysis of psychological and pedagogical literature, advanced pedagogical experience, the key concept of was defined: “emotions” (is a reaction of a preschool child’s personality to internal and external stimuli, with the help of which the child reveals a positive or negative attitude towards people, towards oneself, one’s own actions), “emotional reactions” (is an instant response to various situations, stimuli), “emotional states” (is an arising as a result of an emotional reaction (excitement, depression, fear, anxiety), “emotional perception of the world by preschool children” (is a complex process of forming children’s emotional experience, which includes recognizing emotions and managing them according to moral norms and values in the process of interaction with the world (external and internal), “the world” (is a dynamic, universal phenomenon that combines the external and internal plans of an individual’s life based on one’s subjectivity), which allows them to be considered in the context of modern science to determine the goals and perspectives of emotional perception of the world by preschool children in institutions of preschool education based on a common understanding and using the specified terminology. The types of emotions were identified as the following: primitive and complex, positive and negative, primary and secondary, sthenic and asthenic. Accordingly, the characteristics of emotions are follows: universality, dynamism, polarity, ambivalence, intensity, subjectivity, contagion, switching, recall, irradiation, plasticity, transference. The practical significance of the article is that its materials can be used in organizing institutions of preschool education, training of teachers, psychologists, and students’ pedagogical practice.